Sulfur metabolic engineering enhances cadmium stress tolerance and root to shoot iron translocation in Brassica napus L - Rajab, Hala; Khan, Muhammad Sayyar; Wirtz, Markus; Malagoli, Mario; Qahar, Fariha; Hell, Rüdiger (Plant physiology and biochemistry, 2020)
Serine acetyltransferase (SAT) (EC 2.3.1.30) is the rate-limiting enzyme of cysteine (Cys) biosynthesis, providing the decisive precursor for the ubiquitous defense thiol glutathione (GSH). Together with O-acetylserine (thiol) lyase (OAS-TL; EC 2.5.1.47) SAT generates Cys in the cytosol, plastids, and mitochondria of vascular plants. The current study aimed to overproduce Cys and GSH for enhanced stress tolerance via overexpression of the feedback-insensitive isoform of serine acetyltransferase from tobacco, i.e., NtSAT4. Constitutive overexpression of NtSAT4 in Brassica napus resulted in the 2.6-fold-4-fold higher SAT activity in different subcellular compartment-specific lines. This higher SAT activity led to a 2.5-fold-3.5-fold higher steady-state level of free Cys and 2.2-fold-5.3-fold elevated level of GSH in leaves compared with nontransformed plants. Among the compartment-specific lines, the mitochondrial targeted NtSAT4 overexpressor line M-182 showed the highest levels of Cys (3.5-fold) and GSH (5.3-fold) compared with wild-type plants. Overexpression of NtSAT4 conferred a physiological advantage in terms of enhanced tolerance against oxidative stress with hydrogen peroxide and the heavy metal cadmium (Cd). The NtSAT4 overexpressor lines showed a significantly higher amount of iron (Fe) translocation from roots to shoots compared with nontransformed plants. Overall, these results suggest that overexpression of NtSAT4 is a promising approach to creating plants with tolerance to heavy metals and oxidative stress and, in addition, may potentially improve plant nutrition in terms of enhanced Fe translocation from roots to shoots.
Gesehen am 22.03.2021